Pengaruh Kegiatan Berkebun terhadap Keterampilan Proses Sains pada Anak Usia 5-6 Tahun di TK Santo Fransiskus Asisi Percut - Clara Agustina Siregar (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
The aim of this research is to find out how gardening activities influence the science process skills of students aged 5 to 6 years at the Santo Fransiskus Asisi Percut Kindergarten. The research method used was pre-experimental with a One Group Pretest-Posttest Design. The population of this study consisted of 22 children from group B. Using the saturated sampling method, the sample for this study consisted of 22 children. Data was collected using a structured science process skills observation sheet, then the data was analyzed using the Wilcoxon test. This research found that children at the Santo Fransiskus Assisi Percut Kindergarten, aged between 5 and 6 years, gained significant benefits from gardening activities in developing their science process skills. Based on the results of this research, it is recommended that teachers use gardening activities to further develop science process skills.